Coffee Processing Technology: From Waste to Value - Rucitra Widyasari; Yuhendra AP; Satrijo Saloko; Murad Murad; Sukmawaty Sukmawaty; Rahmat Sabani; Joko Sumarsono; I Wayan Sweca Yasa; Ansar Ansar; Wiharyani Werdiningsih; Made Gendis Putri Pertiwi; Reza Kusuma Nurrohman; Endang Purnama Dewi; Yesica Marcelina Romauli Sinaga; Diah Ajeng Setiawati; Isnaini Puspitasari; Wenny Amaliah; Tri Isti Rahayu; Lingga Gita Dwikasari; Firman Fajar Perdana; Ince Siti Wardatulatifah S; Fuad Sauqi Isnain; Mi’raj Fuadi; Fakhrul Irfan Khalil; Rini Nofrida; Yeni Sulastri; Hary Kurniawan; Qabul Dinanta Utama; Agriananta Fahmi Hidayat; Gagasage Nanaluih De Side; Setyaning Pawestri; Rosnah Shamsudin; Zanariah Mohd Dom; Nur Hamizah Abdul Ghani; Revata Anwar; Attar Riza Maulana; Surya Ananda Firmansyah; I Kadek Widi Widiastawan; Ingka Wira Yuda (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Coffee is one of the most widely traded agricultural commodities globally, generating substantial volumes of by-products and waste streams throughout its processing chain. These by-products including coffee pulp, cascara, mucilage, parchment, silverskin, and spent coffee grounds represent a significant environmental burden when improperly managed, yet simultaneously constitute a rich reservoir of bioactive compounds and valorizable biomass. This manuscript presents a community engagement initiative focused on disseminating and implementing coffee processing technologies that transform waste streams into value-added products, aligned with circular bioeconomy principles. The activity was conducted on 22 April 2026 with participants are small and medium enterprises (SMEs) KWT Kaki Rinjani in Karang Sidemen Village, Central Lombok with the . The session was delivered directly by Prof. Rosnah Shamsudin that introduced aerospace 3.0 the latest small-scale coffee press from UPM. accompanied with theoretical presentation technique drying of coffee, waste treatment and sensory demonstration of functional coffee conducted from Fatepa-Unram. The expected outcomes include enhanced technical and entrepreneurial capacities among SME actors, improved ability to design functional coffee product, and waste treatment of coffee into valuable product. The long-term impact is the creation of a more resilient SMEs ecosystem in Karang Sidemen Village, with a portfolio of functional, high-value coffee products. Furthermore, optimizing the management of production waste is projected to significantly reduce environmental burdens while opening up new income diversification opportunities for the community. Ultimately, the sustainability of this program will strengthen local coffee's position as a leading commodity managed innovatively, efficiently, and environmentally friendly.